Design, implementation and evaluation of a workshop on basic teaching-learning skills for the College of Allied Medical Professions Faculty, University of the Philippines Manila - Cabatan, Ma. Concepcion C.
The purpose of the study was to design, implement and evaluate a workshop on basic teaching-learning skills conducted in May 30-June 1, 1994. Workshop participants consisted of 13 faculty members of the College of Allied Medical professions, University of the Philippines, Manila. The workshop content addressed the following teaching-learning concepts namely: creating learning conditions, writing learning objectives, using appropriate learning activities and resources, evaluating students and showing concern for students. Short lectures, small group activities, individual exercises, and role play constituted the workshop activities. The study used questionnaires, interviews and a review of workshop output to evaluate the effects of the workshop. The faculty self-rating questionnaire contained items addressing the six components covered in the workshop. It also contained an added component that addressed the faculty's perceptions toward teaching. The student's evaluation questionnaire asked students to describe their learning experience in terms of the six components addressed in the workshop. The 13 participants were interviewed two months after the workshop asking them for specific measures they have done to improve their teaching. Group lesson plans written by the participants were reviewed and evaluated using a checklist. Data obtained from the faculty self-rating scores before and after the workshop was subjected to a t-test for matched groups. Results revealed significant improvements after the workshop specifically in the first six components. Only in one component, perception toward teaching, showed no significant change. The quantitative data was mostly corroborated by the qualitative data obtained from faculty and students. Effects of the workshop were highly related to the defined objectives of the workshop. The workshop succeeded in increasing knowledge, raising awareness and interest in improving their teaching among the faculty participants. Results of the study show that there is a need for more teaching improvement workshops that are more specific in nature. The content of future workshops will depend on faculty needs. It is recommended that long term effects of future workshops are studied, i.e. if improvements and/or changes are sustained over a long period of time. Factors that facilitate and/or hinder the faculty from implementing changes in their teaching should be studied in the future. Direct observation, in addition to student questionnaires and teacher self assessments, is also a recommended method for evaluating future workshops on teaching improvement.